Differentiated Learning Strategies at Batealit 2 elementary school Jepara - Niswah, Nihlatun (Contemporary Education and Community Engagement (CECE), 2025)
The diversity of characteristics and learning styles among elementary school students requires educators to create enjoyable and meaningful learning experiences. Differentiated instruction has become one of the models implemented in the Merdeka Curriculum, allowing students the freedom to choose their learning styles. The point of this study is to look into how important differentiated learning is at Batealit 2 elementary schools so that teachers can figure out how to use it with students who have different needs and ways of learning. a qualitative descriptive method in this study is qualitative descriptive with a case study approach. We collected data through direct observation, interviews, and document analysis. The results indicate that the learning strategy employed to create meaningful learning experiences for students is through differentiated instruction. The learning process takes into account the diverse characteristics and learning styles of the students. There are three learning styles among the fourth-grade students at Batealit 2 elementary school: visual, auditory, and kinesthetic, which encourages educators to create learning experiences tailored to the children's learning styles. Through differentiated instruction, students have the opportunity to explore their identities, abilities, skills, and knowledge.